Community perceptions and valuation of freshwater ecosystem services: A case of rural springs - Jeki Saputra; Aminuddin Mane Kandari; La Ode Midi; La Baco Sudia; La Gandri; Herlan Hidayat; Muhammad Saleh Qadri (Interaction, Community Engagement, and Social Environment, 2026)
Background: This study aims to analyze public perception and conduct an environmental service valuation of the Puta Spring in Lakapodo Village, Watopute District, Muna Regency. Methods: The study was conducted from April to June 2024 with a population of 318 households that use the Puta Spring as their main water source. The research sample was determined using the Slovin formula with a confidence level of 10%, resulting in 76 respondents selected through purposive sampling, with the criterion of people who had used the spring for at least the last five years. Data were collected through observation, interviews, and literature studies, then analyzed descriptively and quantitatively. Findings: The results showed that the community's perception of the existence of Puta Spring was in the good category with an average score of 242.47. This indicates a high level of awareness of the importance of preserving this water source in supporting daily needs. The valuation of environmental services calculated based on the prevailing price method shows an economic value of IDR 211,104,000.00 per year, while based on the market price in Muna Regency, it reaches IDR 164,661,120.00 per year. The total volume of water used for domestic needs by the entire community of Lakapodo Village is 42,220.8 m³ per year, with an average discharge of Puta Spring of 0.0082 m³/second. Conclusion: Public perception of the spring is generally good, with high scores in existence, management, utilization, and economic value. Water availability exceeds community use, resulting in a surplus of 212,283 m³/year, corresponding to an economic value of IDR 1,061,415,000, indicating sustainable resource potential. Novelty/Originality of this article: The novelty of this study lies in integrating community perception assessment with economic valuation and water balance analysis to reveal the surplus value and sustainability potential of the Puta spring.